2-Hydroxy-3-chloro-5-ethylacetophenone Oxime as an Analytical Reagent for Copper(II) - I. Desai, Suketu; A. Desai, Vikas; Naik, H.B. (Asian Journal of Chemistry, 2010)
2-Hydroxy-3-chloro-5-ethylacetophenone oxime was developed as new analytical reagent for gravimetric estimation of copper and for its separation from other ions. The buff precipitation of copper(II) by the reagent is complete between pH 3.0 to 9.0 and after drying at 110-120 ºC the composition of the precipitation corresponds to Cu(C10H11O2NCl)2. It is also observed that by proper control of pH and by using suitable masking agents, it is possible to estimate copper in presence of other interfering ions.